2016
DOI: 10.1371/journal.pone.0149370
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Hedgehog Signaling Synergistically Increases Sensitivity to Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors in Non-Small-Cell Lung Cancer Cell Lines

Abstract: Aberrant activation of the hedgehog (Hh) signaling pathway has been implicated in the epithelial-to-mesenchymal transition (EMT) and cancer stem-like cell (CSC) maintenance; both processes can result in tumor progression and treatment resistance in several types of human cancer. Hh cooperates with the epidermal growth factor receptor (EGFR) signaling pathway in embryogenesis. We found that the Hh signaling pathway was silenced in EGFR-TKI-sensitive non-small-cell lung cancer (NSCLC) cells, while it was inappro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 51 publications
3
57
0
1
Order By: Relevance
“…Infact, protein lysates from harvested resistant tumors showed higher vimentin levels and EGFR-inhibitors resistant cancer cells established in vitro showed high invasive and migrative abilities. Consistently with our previous findings, Hh signaling was confirmed as an important mediator of resistance to EGFR-TKIs inhibitors for first-generation EGFR-TKIs [6, 3032]. Further, in the present study, we demonstrated that Hh activation is involved also in resistance to second and third generation EGFR-TKIs.…”
Section: Discussionsupporting
confidence: 93%
“…Infact, protein lysates from harvested resistant tumors showed higher vimentin levels and EGFR-inhibitors resistant cancer cells established in vitro showed high invasive and migrative abilities. Consistently with our previous findings, Hh signaling was confirmed as an important mediator of resistance to EGFR-TKIs inhibitors for first-generation EGFR-TKIs [6, 3032]. Further, in the present study, we demonstrated that Hh activation is involved also in resistance to second and third generation EGFR-TKIs.…”
Section: Discussionsupporting
confidence: 93%
“…Deregulated Sonic Hedgehog (SHH) pathway facilitates the initiation, progression and metastasis of NSCLC, confers drug resistance against targeted therapy and renders a lung cancer therapeutic interference option to cancer patients with poor prognosis 3638 . Substantial studies have proved close relationship between aberrantly activated Hedgehog cascaded and chemo-drug resistance in lung cancer while downregulation of SHH pathway resensitizes cancer cells to conventional chemotherapy 7, 18, 20, 39, 40 .…”
Section: Discussionmentioning
confidence: 99%
“…33 However, a previous study reported that restoring E-cadherin expression can increase sensitivity to EGFR-TKIs. 34 The miRNAs identified in our study serve as markers to predict the mechanisms of acquired drug resistance in NSCLC without biopsy. The enforced miR-149-5p expression significantly induced the resistance of acquired-resistant cells to gefitinib treatment.…”
Section: Discussionmentioning
confidence: 89%